2020
DOI: 10.1109/access.2020.3028741
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Analysis of the One Compartment Pharmacokinetic Model Considering Optimal Controls

Abstract: First-order 1-compartment pharmacokinetic model for extravascular administered drugs can be used to derive many useful quantities by comparing the predicted values with actual data. However, less research has been done in actually formulating them as optimal control problems. Moreover, real pharmacological processes are always exposed to influences that are not completely understood or not feasible to model explicitly. Ignoring these phenomena in the modeling may affect the estimation of PK/PD models' (pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Drug concentration levels in the body vary among different patients according to their weight, age, stress, or genetic factors [1]. In addition, it has also been observed that the food intake, special excercises and some vitamin can affect the drug absorption [2]. Due to the variability and uncertainty of such factors, several researches have introduced stochastic corrections on the well known compartmental pharmacokinetics deterministic models [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug concentration levels in the body vary among different patients according to their weight, age, stress, or genetic factors [1]. In addition, it has also been observed that the food intake, special excercises and some vitamin can affect the drug absorption [2]. Due to the variability and uncertainty of such factors, several researches have introduced stochastic corrections on the well known compartmental pharmacokinetics deterministic models [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the problem to determine an optimal dosing timing schedule to control the blood drug concentration is studied in [2]. The authors combine optimal control theory and stochastic methods, prove existence, uniqueness of the solution and present the corresponding stability analisys.…”
Section: Introductionmentioning
confidence: 99%
“…We augmented the ODE PK one‐compartment model as an SDE PK model in Liu and Shan 23 . In this paper, we build a new two‐compartment PK model for IV administration by integrating optimal control theory and stochastic analysis.…”
Section: Introductionmentioning
confidence: 99%